Improving the LGBTQ2S+ cultural competency of healthcare trainees: advancing health professional education - Lee, Matthew; Tasa-Vinyals, Elisabet; Gahagan, Jacqueline (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Background: Lesbian, Gay, Bisexual, Trans, Queer, and Two-spirit (LGBTQ2S+) populations experience worse health outcomes compared to age-matched heterosexual and cisgender peers. Health professionals’ deficient knowledge and negative attitudes can contribute to these inequities. Healthcare trainees report insufficient LGBTQS2+ cultural competence training.Methods: In this prospective, mixed-methods pre-post design, Atlantic Canadian health students were tested on knowledge, attitudes and self-reported behaviours towards LGBTQ2S+ populations in healthcare settings. Assessment included psychometric measurements and clinical cases involving normative and non-normative fictional patients. Participants were randomised to intervention or control groups. The intervention consisted of three training sessions lead by LGBTQ2S+ experts and elders from the community. The control group continued with usual training. Full assessment was repeated after training. We also held focus group discussions with students and faculty.Results: The intervention group significantly improved attitudes toward and knowledge of LGBTQ2S+ populations and changed relevant aspects of their performance in the simulated clinical situations. Focus groups identified key gaps in current local training.Conclusions: Integrating specific training related to LGBTQ2S+ health within health professions programs is an important step toward improving these populations’ accessibility to a competent, exhaustive and nurturing healthcare. Additional research on innovative means to expand and broaden the scope of our training is warranted.